The Fermentation of a Marine Probiotic Bacterium on Low-Cost Media Formulated with Industrial Fish Gelatin Waterstreams and Collagen Hydrolysates - José Antonio Vázquez; Adrián Pedreira; Iván Salmerón; Dyah H. Wardhani; Jesus Valcarcel (Processes, 2023)
Chemical effluents generated by the isolation of fish gelatin and collagen hydrolysates produced from the enzyme proteolysis of skin wastes are protein-rich substrates that could be used as nutrients in bacterial bioprocessing. In this study, the suitability of such nutrients in supporting the growth of a marine probiotic bacterium, Phaeobacter sp. DIFR 27-4, was studied. Both gelatin effluents and collagen hydrolysates were obtained from the skins of shark, tuna, salmon and turbot. The chemical composition of the substrates included the complete presence of all quantified amino acids. Low-cost marine culture media were formulated with these protein materials alongside a very low concentration of yeast extract and marine water. In batch cultures with gelatin effluents, the growth rates of the strain DIFR 27-4 were somewhat lower than those found in the control marine commercial media. In the case of the hydrolysates, the bacterial production of biomass was similar or higher than that observed in the control, and larger than that observed in the effluents. A simple evaluation of production costs in the different substrates studied indicated that around a 73–125-fold reduction can be achieved when alternative media are used, in comparison to the use of commercial marine broth.